2015
DOI: 10.4309/jgi.2015.31.9
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Gambler and his Spouse: How do their Narratives Match?

Abstract: This case study compares the narratives of a pathological gambler and his spouse concerning family, marital and individual matters. It does so through identifying each of the key players' narratives individually (analysis of self-report questionnaires) and interactively (couples therapy sessions analysis). The results show that the gambler has a rather more positive view of gambling-related issues than does his spouse, and this fact is most apparent when it comes to marital and family issues. The gambler's per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Women may also be more able to place respectable limits around their capacity to care: 'One of the main things that (my therapist) had said to me was that I'm not his therapist' (family member interviewed by Kourgiantakis et al, 2018, p. 301). This validation of women's personal boundaries and safety concerns seems important in light of persistent findings that people with gambling issues tend to downplay and/or deny the impact that their behaviour has on their significant others (Cunha et al, 2015;Landon et al, 2018;Patford, 2009). The question of whether or not to leave an abusive and/or violent relationship is highlighted as a key struggle for women with gambling partners, particularly those with children Patford, 2009).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Women may also be more able to place respectable limits around their capacity to care: 'One of the main things that (my therapist) had said to me was that I'm not his therapist' (family member interviewed by Kourgiantakis et al, 2018, p. 301). This validation of women's personal boundaries and safety concerns seems important in light of persistent findings that people with gambling issues tend to downplay and/or deny the impact that their behaviour has on their significant others (Cunha et al, 2015;Landon et al, 2018;Patford, 2009). The question of whether or not to leave an abusive and/or violent relationship is highlighted as a key struggle for women with gambling partners, particularly those with children Patford, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Given their involvement in promoting or hindering the recovery processes, women have emerged as key 'intervention allies.' Concepts such as 'denial,' 'conformism,' and 'social desirability' (e.g., as deployed by Cunha et al, 2015), and 'codependence' (see critiques by Calderwood & Rajesparam, 2014;Orford, 2014) have been drawn on to position women as negligently avoiding and/or contributing to the gambling problem (see Cunha et al, 2015). Tools and recommendations for improving FAOs' abilities to support their gambler's recovery have been developed; for example, the CRAFT program adopts therapeutic techniques developed for FAOs of substance abusers, helping to persuade the gambler to enter treatment, reduce gambling behaviour, and assisting FAOs with their own personal functioning (Makarchuk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…At the methodological level, no studies have as yet taken into consideration the PGs' viewpoint, which would be an additional tool for measuring the degree of coherence between the perceptions of the two members of the couple as to how partners employ strategies. Moreover, studies of couples where one is a PG have revealed the distinctions in the perceptions between the PG and the partner Cunha, Sotero, & Relvas, 2015;Ferland et al, 2008). Furthermore, while certain authors have noted the evolution over time in adaptation strategies (Bruchon-Schweitzer, 2001;De Ridder,1997;Lazarus & Folkman, 1984;Paulhan, 1992), little information has been collected about the strategies used by PGs' partners.…”
Section: Transactional Model Of Stress and Copingmentioning
confidence: 99%
“…Estudo 4 -The pathological gambler and his spouse: How do their narratives match? (Cunha, Sotero, & Relvas, 2015) Este trabalho compara as narrativas de um jogador patológico e do seu cônjuge (estudo de caso) sobre aspetos familiares, conjugais e individuais, através da identificação das narrativas de cada um dos protagonistas individualmente (análise de questionários de autorrelato -os mesmos referidos no Estudo 1) e em interação (análise das sessões de terapia de casal/processo terapêutico). A narrativa do cônjuge é mais representativa nas dimensões stress familiar (66.67%) e dificuldades da conjugalidade (85%) e, em particular, nos temas dificuldades de comunicação e partilha emocional (85%), dificuldades na partilha das tarefas do quotidiano (90%), dificuldades na intimidade sexual (80%), peso da desconfiança na conjugalidade (87.50%) e desafios familiares (75%).…”
Section: Estudo 3 -Professional Gamblers: Psychopathology Individualunclassified